2003
DOI: 10.1029/2002ja009822
|View full text |Cite
|
Sign up to set email alerts
|

Study of the ionospheric total electron content response to the great flare on 15 April 2001 using the International GPS Service network for the whole sunlit hemisphere

Abstract: [1] The characteristics of the ionospheric response to the solar flare on Apr. 15, 2001 were studied using the total electron content (TEC) obtained at GPS observational stations in the whole sunlit hemisphere under International GPS Service for Geodynamics. It was found that the largest enhancement of the sudden increase of total electron content during this flare is $2.6 TECU (1 TECU = 10 16 m À2 ). The effects of solar flare radiation on the ionosphere can be recognized even in the region at 0600 or 1800 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 43 publications
4
35
1
Order By: Relevance
“…[17] It has been well known that solar flare-induced SITEC values depend on the SZA [Zhang and Xiao, 2003;Tsurutani et al, 2005;Wan et al, 2005]. Tsugawa et al [2006a] statistically analyzed 91 SITEC events from January 2000 to May 2005 using the worldwide GPS receiver network and revealed that the SITEC value is linearly dependent on the cosine of SZA with nonnegligible residuals in almost all the flare events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] It has been well known that solar flare-induced SITEC values depend on the SZA [Zhang and Xiao, 2003;Tsurutani et al, 2005;Wan et al, 2005]. Tsugawa et al [2006a] statistically analyzed 91 SITEC events from January 2000 to May 2005 using the worldwide GPS receiver network and revealed that the SITEC value is linearly dependent on the cosine of SZA with nonnegligible residuals in almost all the flare events.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of 21st century, the twodimensional imaging technique using TEC data from worldwide GPS receiver networks has been applied to SITEC studies [e.g., Afraimovich et al, 2001;Liu and Lin, 2004]. These studies have observed a solar zenith angle (SZA) dependence of SITEC [Zhang and Xiao, 2003;Wan et al, 2005]. Tsugawa et al [2006a] statistically analyzed 91 clear SITEC events from January 2000 to May 2005 and revealed the summer-winter hemispheric asymmetry (SWHA) of SITEC is due to that of the O/N 2 density ratio in the ionospheric F region.…”
Section: Introductionmentioning
confidence: 99%
“…Most ionosphere responses to solar flares have been attributed to, and can be explained by, the enhancement of solar X-rays and EUV during solar flares. For example, it has been found that total electron content (TEC) enhancement during solar flares primarily follows the cosine of solar zenith angle [Zhang and Xiao, 2003;Liu et al, 2007;. However, recent measurements have revealed phenomena that may not be attributable to or cannot be explained by solar irradiance and related physical and chemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the duration of TEC enhancements is lasting several hours, that is much longer than the flare duration. On the other hand, a high correlation was found between the rate of TEC variations and hard X-ray variations observed by Yohkoh in the band of 53-93 keV (Afraimovich et al, 2001;Zhang and Xiao, 2003). In other words, the fast TEC variations are closely related to the solar hard electro- magnetic emission while their gradual changes are different.…”
Section: Introductionmentioning
confidence: 90%